Answer:
Step 3.
Explanation:
We have the equation,
![(1)/(4)(12x+8)+4=3](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ti6mnmrjf8mgyx0pvtfwlcsftn51u3aelw.png)
Step 1:
..........Opened the brackets on the left side.
Step 2: 3x + 6 = 3..............Added the numbers on the left.
Step 3: 3x = -3...............Subtracted both sides by 6.
Step 4: x = -1....................Divided both sides by 3.
Thus, we can see that,
Step 3 shows the result of applying the subtraction property of equality.